Comparing the Effects of Live and Pasteurized Akkermansia muciniphila on Management of Obesity and Diabetes - Arefeh Shahriary; Zahra Hoseini-Tavassol; Ahmad-Reza Soroush; Hanieh-Sadat Ejtahed; Bagher Larijani (Journal of Mazandaran University of Medical Sciences, 2021)
Diabetes and obesity are among the most important metabolic disorders which are of worldwide concern. Today, it has been proven that the diversity and composition of the intestinal microbiota play a key role in the incidence and control of metabolic diseases via regulating the metabolism and immune responses of the host. Previous studies reported links between Akkermansia muciniphila, a commensal bacterium in the gut microbiota, and obesity and diabetes. Human and animal studies have shown that this mucin-degrading bacterium is effective in preventing obesity and diabetes by reducing intestinal wall permeability and preventing metabolic endotoxemia and inflammation, as well as modulating energy and fat metabolism. New evidence shows that both forms of the A. muciniphila (live bacterium or its pasteurized form) can control the disease. Considering the difficulties of the survival and cultivation of this anaerobic bacterium and in order to help optimal use of A. muciniphila in clinical treatments of metabolic diseases, in this study we compared the effect of live and pasteurized A. muciniphila. Besides, we investigated the effects of this bacterium as the next generation of probiotics on obesity and management of diabetes.